Layered compounds based on molybdenum disulfide and ruthenium arene complexes - Golub, Alexandre S.; Shumilova, Inna B.; Zubavichus, Yan V.; Jahncke, Manfred; Süss-Fink, Georg; Danot, Michel; Novikov, Yurii N. (My University, 1997)
Intercalation compounds of MoS2 with monomeric or OH-bridged dimeric ruthenium arene cationic complexes have been obtained by interaction of MoS2 single-layer dispersions with aqueous solutions of [(arene)Ru(H2O)3 ]SO4 [arene=C6H6 , C6H2Me4-1,2,4,5, C6H4Me-1-Pri-4]. The structural arrangement of these intercalation compounds is discussed on the basis of XRD and EXAFS data. The arene ligands are orientated roughly perpendicular to the MoS2 slabs. Their nature determines the interlayer spacing as well as the intercalated cation content. Heating removes the organic ligands, while ruthenium-containing species remain in the van der Waals space of MoS2.